Land Dispute Settlement: A Key Issue to Ensure Long-lasting Peace in Chattogram Hill Tracts - Siddiqui, Muhammad Ali Haider (UIN Sunan Gunung Djati Bandung, 2024)
Chattogram Hill Tracts (CHT) constitutes nearly 10% of the total landmass of Bangladesh. Extremely beautiful, yet this part of Bangladesh was ravaged by almost 27 years of insurgency. It indeed came to a formal end with the signing of the historic Peace Agreement between the Government of Bangladesh and Parbattya Chattagram Jana Sanghati Samiti (PCJSS) on 02 December 1997. So far, 48 out of the 72 clauses have already been implemented and the rest are in the process. The land issue is one of the major issues that have beset the progress of the agreement. Most communal clashes and unwanted situations usually erupt from disputes over the possession of the land. To settle the land disputes, a commission was formed in 2001 in light of the CHT agreement. The government has recently amended the Land Commission Act 2001 into 2016 as per the demand of the tribal leadership. The amendment has been viewed as discriminatory by the Bengali community, which fears losing their land rights if it is implemented. Against this backdrop, the research was undertaken to identify the probable challenges for the Land Commission to settle the land disputes and suggest a comprehensive modality to resolve the crisis. The study followed a mixed method methodology. During the study, issues like the credibility of the Commission, the land management system in CHT, communal disharmony, absence of a cadastral survey, the security situation, and conflicting issues of the amended Land Commission Act -2016, came out as the major challenges and impediments to the peaceful resolution of land disputes.The study suggests a consensual approach of the Government and concerned stakeholders to address the identified issues in order to resolve land disputes in CHT. As this also bears significant importance in the full implementation of the hard-earned CHT Agreement, any delay in the settlement of land disputes would presumably complicate the situation and likely make the overall security environment of the CHT region unstable once again.